Aplikasi Inventory dengan Metode FIFO dan LIFO Berbasis Web pada PT. Affas Inti Selaras - Naufal, Iqbal Arsalan; Choiron, Achmad; Santoso, Budi (STMIK Banjarbaru, 2025)
PT. Affas Inti Selaras faced inefficiencies in managing medical equipment inventory due to reliance on manual bookkeeping and Microsoft Excel. This study developed a web-based application integrating First-In First-Out (FIFO) for perishable items and Last-In First-Out (LIFO) for non-perishable goods. The system was developed using System Development Life Cycle (SDLC) through stages of requirement analysis, UML (Unified Modeling Language) design, PHP-MySQL implementation, and black-box testing with user acceptance trials. Results demonstrated the application successfully: (1) calculated stock accurately using FIFO/LIFO algorithms, (2) generated real-time transaction reports, and (3) reduced recording discrepancies from an initial 22% to below 5% in system trials. Testing with 10 respondents yielded 82%